Morphological and physiological response of anaerobic granular sludge during the enhanced biohydrogen process via cascade acid stress. (14th September 2015) - Xia, Yan; Zhu, Chunyan; Yan, Qun; Zhao, Mingxing; Zhang, Guangsheng
Abstract Morphological and physiological response of anaerobic granular sludge during the enhanced biohydrogen process via cascade acid stress were investigated. It was found that average granular size of all stress groups declined drastically, along with decreasing of pH after acid stress. Besides, gas pressure within each stress group kept fluctuating during the biohydrogen process, while the hydrogen capability of biogranules achieved about 3 times of the control after acid stress. Moreover, the dehydrogenase activity and hydrogen content reached 7977 μg TF/g TS·h and 34.2% after 60 h of acid stress, while which were only 5741 μg TF/g TS·h and 17.8% for the control group, respectively.